If I do not have love. "Humanoid" Love - Biegalska, Agnieszka (Filozofia Chrześcijańska, 2014)
Is love characteristic only of homo sapiens? Is it only man that can love and be loved? Or has there come the time of the Cyberman – an artificial life partner to have sex with, to love and to marry? The attempt of answer to these questions is based on data collected within exact sciences and humanities, and in particular on the idea of a post-biological man of  transhumanism.